Biomineralization of struvite induced by indigenous marine bacteria of the genus Alteromonas - He, Wei; Xue, Hua-Peng; Liu, Chuang; Zhang, Ai Hua; Huang, Jian-Ke; Zhang, Dao-Feng (Frontiers in Marine Science, 2023)
Biomineralization is a universal phenomenon in the ocean that plays an important role in marine geochemical circulation. The genus Alteromonas is an indigenous taxon with a wide distribution and various ecological roles in the ocean, but biomineralization by this genus has not been reported. In this study, five Alteromonas spp. were found to induce mineral crystal formation of different shapes and sizes in agar media. Further studies on deep-sea strains A. alteriprofundi HHU 13199T and A. alterisediminis N102T showed that they could produce mineral crystals with similar morphology when grown in agar or broth media with different concentrations of sea salts (i.e., 2%, 4%, 6%, and 8%), and that their growth was dependent on Ca2+ and/or Mg2+ ion concentrations. Genomic analysis showed that the genus Alteromonas universally possessed the ammonification metabolism pathway and that, during the culture of these bacteria, the production of mineral crystals was accompanied by an increase in ammonia concentration and pH value and a decrease in nitrate nitrogen concentration. The addition of ammonia to broth media (≈ 572.7 mg/L) simulated the ammonia content in media on days 5 and 6 of bacterial growth and also induced mineral crystals to form. Through the analysis using scanning electron microscope–energy-dispersive spectrometry (SEM-EDS), X-ray diffraction (XRD), Fourier-transform infrared microscopy (FTIR), thermogravimetric (TG) analysis, and differential thermal gravity and differential scanning calorimetry (DTG–DSC), mineral crystals induced by bacterial strains and the non-strain (ammonia-added sample) were all identified as struvite mineral. In addition, the characteristics of the struvite mineral induced by bacterial strains were different from the characteristics of the struvite synthesized by non-strain and of a struvite mineral standard. Thus, this study deduces that Alteromonas spp. possess the ability to induce struvite formation. The mechanism mainly lies in the presence of an ammonification metabolism pathway to produce ammonia, which should be recognized as biologically induced mineralization (BIM). This study provides insight into a new ecological role of indigenous marine taxa of the genus Alteromonas.